Development of angle-independent color material using colloidal amorphous array. (24th July 2019) - Naoi, Yui; Seki, Takahiro; Yoshioka, Shinya; Takeoka, Yukikazu
Abstract: Color materials utilizing physical phenomena such as scattering, diffraction, and interference of light have drawn attention as alternatives to organic dyes that fade by light and some inorganic pigments that are highly toxic. For example, a color material exhibiting structural color caused by a fine structure with a size that is on the order of the wavelength can be prepared using only human body or environmentally friendly materials. If the fine structure is kept stable, the structural colored material can be a nonfading color material. We know that a conventional structural colored material exhibits a property that the hue greatly changes depending on the light irradiation direction and the viewing direction. Recent studies have shown that colloidal amorphous arrays obtained with spherical colloidal particle aggregates with short-range order have almost no angle dependence of the hue under natural light where light is irradiated from all directions. However, the structural color generated from the colloidal amorphous array exhibits angle dependence on the hue under the condition that light is irradiated only from one direction. In this study, we found a light scattering peak, in the scattering spectrum observed from the colloidal amorphous array, showing no angle dependence at all on the shorter wavelength side than the light scattering peak caused by the existence of the short-range order. By exploiting this scattering phenomenon, we will explain the possibility of producing a color material with no angle dependence on the hue even under the condition that light is irradiated only from one direction.